Contextualizing Inflow and Infiltration Within the Streamflow Regime of Urban Watersheds. Issue 1 (24th January 2022) - Pangle, Luke A.; Diem, Jeremy E.; Milligan, Richard; Adams, Ellis; Murray, Allison
Abstract: Defects in sanitary‐sewer infrastructure enable exchange of large volumes of fluids to and from the environment. The intrusion of rainfall and groundwater into sanitary sewers is called inflow and infiltration (I&I). Though long recognized in the assessment of sewers, the impacts of I&I on streamflow within urban watersheds are unknown. We quantified rainfall‐derived I&I (RDI&I), groundwater infiltration (GI), and total I&I using measured flows within sanitary‐sewer pipes serving four watersheds near Atlanta, Georgia, USA. Flows were monitored in pipes that parallel local stream channels and compared with streamflow measured at nearby gauging sites. Freshwater diverted into the sewer system due to I&I ranged from 24% to 36% of the flow measured within individual pipes. The RDI&I was the smaller component of I&I, ranging from 4.2 to 9.8 mm per year among watersheds. The GI was typically an order of magnitude greater than RDI&I, ranging from 24 to 41 mm per year among watersheds with annual stream discharge of approximately 500 mm. The I&I occurring at specific moments in time commonly represented 0%–20% of the flow measured in the adjacent stream. The enhancement of low flows in streams that could be achievable if I&I were abated ranges from as much as 6%–36% across watersheds. Our discussion presents explanations for the seasonality of I&I and associated impacts on streamflow in urban watersheds, while identifying important sources of remaining uncertainty. Our results support the conclusion that I&I substantially reduces flows in urban streams, especially low flows during dry weather. Plain Language Summary: Water infrastructure degrades over time, allowing for the movement of large volumes of fluids to and from the environment. Inflow is the flow of precipitation into sanitary‐sewer pipes through, for example, leaky manholes and gutter downspouts. Infiltration is the flow of groundwater into the same pipes through fractures, leaky joints, and other defects. They cause overflows of untreated sewage that endanger humans and ecosystems. Inflow and infiltration also represent large diversions of fresh water away from local streams. We examined rates of flow in four sanitary‐sewer pipes and quantified the inflow and infiltration. We compared these estimates to the rates of flow in nearby streams. We find that inflow and infiltration of fresh water into sanitary‐sewer pipes commonly represent 20%–40% of the flow in the pipes. Most of that water emanates from aquifers with a smaller fraction supplied by precipitation. If the inflow and infiltration were abated, and that fresh water instead flowed to stream channels, then the flows in those channels during dry periods could be enhanced by as much as 6%–36%. This is important in urban watersheds, where streamflow during dry weather is already diminished. Inflow and infiltration represent infrastructure‐mediated flow pathways that substantially alter the water cycle in urban watersheds. Key Points: Large volumes of precipitation and ground water flow into sanitary‐sewer pipes This undesirable diversion of water substantially reduces flow in urban streams Abatement of this problem could enhance low flows in urban streams by 6%–36%